Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1155/2022/4934190
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Design of Intelligent Diagnosis and Treatment System for Ophthalmic Diseases Based on Deep Neural Network Model

Abstract: Artificial intelligence (AI) has developed rapidly in the field of ophthalmology. Fundus images have become a research hotspot because they are easy to obtain and rich in biological information. The application of fundus image analysis (AI) in background image analysis has been deepened and expanded. At present, a variety of AI studies have been carried out in the clinical screening, diagnosis, and prognosis of eye diseases, and the research results have been gradually applied to clinical practice. The applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…[37,38] For example, fundus images have become a research hotspot due to their ease of acquisition and rich biological information. [39] AI research in health care, specifically machine learning and deep learning, has definite clinical relevance in ophthalmology. [40,41] The yearly growth of AI in ophthalmology publications has been 18.89% over the last 10 years [43] and was verified over the last 4 years in this study (at the bottom of Fig.…”
Section: Additional Informationmentioning
confidence: 99%
“…[37,38] For example, fundus images have become a research hotspot due to their ease of acquisition and rich biological information. [39] AI research in health care, specifically machine learning and deep learning, has definite clinical relevance in ophthalmology. [40,41] The yearly growth of AI in ophthalmology publications has been 18.89% over the last 10 years [43] and was verified over the last 4 years in this study (at the bottom of Fig.…”
Section: Additional Informationmentioning
confidence: 99%
“…Using the Madrid and Zaragoza test suite for the dataset, the highest accuracy achieved was 0.92 with VGG19, while MobileNet had the lowest accuracy of 0.77. Another study by Zhou (2022) [20] used the M-ResNet model to develop an intelligent system for diagnosing cataracts, subconjunctival haemorrhage, keratitis, and pterygium. The results demonstrated the system's effectiveness, with the best accuracy reaching 0.875.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%